Effect of Slope and Distance from Oil Palm Stands on Soil Water Content - Siringoringo, Naomi Yulia; Gusmara, Herry; Prawito, Priyono; Prasetyo, Prasetyo; Utami, Kartika (BPFP Universitas Bengkulu, 2023)
This study aims to study the effect of land slope and distance from the main crops on soil water content at the end of the rainy season. The research location is located at position 3°41'51.8